Efficacy of preventive use of oxygen therapy after planned extubation in high-risk patients with extubation failure: A network meta-analysis of randomized controlled trials - Zheng, Xiaozhuo; Wang, Rui; Giri, Mohan; Duan, Jun; Ma, Mengyi; Guo, Shuliang (Frontiers in Medicine, 2022)
Background: Extubation failure is common in critically ill patients, especially those with high-risk factors, and is associated with poor prognosis. Prophylactic use of oxygen therapy after extubation has been gradually introduced. However, the best respiratory support method is still unclear. Purpose: This study aimed to evaluate the efficacy of four post-extubation respiratory support approaches in reducing reintubation and respiratory failure in patients at high-risk of extubation failure. Methods: A comprehensive search was performed in Cochrane Central Register of Controlled Trials, PubMed, EMBASE, and Web of Science from inception to June 2022. Randomized controlled trials (RCTs) comparing post-extubation preventive use of respiratory management strategies, including conventional oxygen therapy (COT), noninvasive ventilation (NIV), and high-flow nasal catheter (HFNC) in high-risk patients with extubation failure were reviewed. Primary outcomes were reintubation rate and respiratory failure. Secondary outcomes included intensive care unit (ICU) mortality, ICU stay and length of hospital stay (LOS). Results: Seventeen RCTs comprising 2813 participants were enrolled. Compared with COT, the three respiratory support methods (NIV, HFNC, NIV+HFNC) were all effective in preventing reintubation (odds ratio (OR) 0.46, 95% confidence interval (CI) 0.32-0.67; OR 0.26, 95% CI 0.14-0.48; OR 0.62, 95% CI 0.39-0.97, respectively) and respiratory failure (OR 0.23, 95% CI 0.10-0.52; OR 0.15, 95% CI 0.04-0.60; OR 0.26, 95% CI 0.10-0.72, respectively). NIV and NIV+HFNC also reduced ICU mortality (OR 0.40, 95% CI 0.22-0.74; OR 0.32, 95% CI 0.12-0.85). NIV+HFNC ranked best in terms of reintubation rate, respiratory failure and ICU mortality based on the surface under the cumulative ranking curve (SUCRA) (99.3, 87.1, 88.2, respectively). Although there was no significant difference in shortening ICU stay and LOS among the four methods, HFNC ranked first based on the SUCRA. Conclusions: Preventive use of NIV+HFNC after scheduled extubation is probably the most effective respiratory support method for preventing reintubation, respiratory failure and ICU death in high-risk patients with extubation failure. HFNC alone seems to be the best method to shorten ICU stay and LOS.